Historians Respond to Whitehouse et al. (2019), "Complex Societies Precede Moralizing Gods Throughout World History". (31st December 2018) - Slingerland, Edward; Monroe, M. Willis; Sullivan, Brenton; Walsh, Robyn; Veidlinger, Daniel; Noseworthy, William; Herriott, Conn; Raffield, Ben; Peterson, Janine; Rodríguez, Gretel; Sonik, Karen; Green, William; et al.
Abstract : As historians, archaeologists, and database analysts affiliated with the Database of Religious History (DRH; religiondatabase.org), we share with the Seshat: Global History Databank team, authors of a recent study published in Nature, an excitement about the potential for deep and sustained collaborations between historians and analysts to answer big questions about human history. We have serious concerns, however, by the approach to the quantitative coding of historical data taken by the Seshat team, as revealed in the backing data (seshatdatabank.info/nature), as well as by a lack of clarity concerning the degree of involvement of expert historians in the coding process. The apparent lack of appreciation for historical scholarship that this coding strategy displays runs the risk of permanently alienating the community of academic historians, who are essential future collaborators in any project devoted to large-scale historical data analysis. In the present commentary, we present a preliminary critical review of their latest article, "Complex Societies Precede Moralizing Gods Throughout World History" (2019).